2015
DOI: 10.2217/fmb.15.5
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B3 Replication and Pathogenesis

Abstract: Viruses such as coxsackievirus B3 (CVB3) are entirely host cell-dependent parasites. Indeed, they must cleverly exploit various compartments of host cells to complete their life cycle, and consequently launch disease. Evolution has equipped this pico-rna-virus, CVB3, to use different strategies, including CVB3-induced direct damage to host cells followed by a host inflammatory response to CVB3 infection, and cell death to super-additively promote target organ tissue injury, and dysfunction. In this update, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
174
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(192 citation statements)
references
References 254 publications
(262 reference statements)
0
174
0
15
Order By: Relevance
“…73 The pathogenic processes discussed here are recognized to be downstream of the encounter between host and virus that includes an enteric portal and involvement of the immune system structurally and functionally at early points in the deadly duel of virus and host. 74,75 …”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…73 The pathogenic processes discussed here are recognized to be downstream of the encounter between host and virus that includes an enteric portal and involvement of the immune system structurally and functionally at early points in the deadly duel of virus and host. 74,75 …”
Section: Mechanismsmentioning
confidence: 99%
“…Multiple cellular signaling pathways are known to be activated upon viral infection and play a critical role in regulating viral infectivity at various steps of viral lifecycle, including viral entry, replication, release, and evasion from host immune responses. 75 Coyne and Bergelson 84 demonstrated that viral entry into epithelial cells through tight junctions is mediated by Fyn and Abl kinases. Studies have also revealed that the activation of the tyrosine protein kinase p56 lck , a member of the Src family kinases, the extracellular signalregulated kinase 1/2 mitogen-activated protein kinase, and protein kinase B signaling as a result of CVB3 infection of immune and myocardial cells is required for efficient viral replication and is associated with host susceptibility to viral myocarditis.…”
Section: Virus-induced Direct Damagementioning
confidence: 99%
“…injection, CVB3 replicates to high titers in tissues and causes disease similar to that observed in humans (12)(13)(14), and male mice are more likely to develop severe myocarditis than female mice. Experimental evidence suggests that two mechanisms contribute to CVB3-induced myocarditis in these mouse models: direct viral lysis of infected cardiomyocytes and immunemediated damage of cardiac tissue (15). The latter is hypothesized to be responsible for the sex bias in disease.…”
mentioning
confidence: 97%
“…The life cycle of enterovirus begins with recognition and binding to receptors on plasma membrane, followed by receptor-mediated endocytosis which results in virus uncoating and release of viral genome RNA (vRNA) into cytoplasm induced by pH change in endosomal compartment [68,69]. Subsequently, vRNA serves as a primary template to translate into a large polyprotein that are cleaved by viral proteases 2A pro , 3C pro and 3CD pro into ten proteins, including four capsid proteins (VP1, VP2, VP3 and VP4), two viral proteases (2A, and 3C), a RNA-dependent-RNA-polymerase (3D), two proteins involved in RNA synthesis (2B, and 2C), and a primer of initiation of RNA synthesis (3AB) [68,69].…”
Section: Enterovirus: Pathogenesis and Life Cyclementioning
confidence: 99%